Risk of Cirrhosis in Patients with Non-alcoholic Fatty Liver Disease and Previous Viral Hepatitis B - S. N. Batskikh; E. V. Vinnitskaya; E. S. Sbikina; Zh. V. Borunova; A. S. Dorofeev; Yu. G. Sandler (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Previous viral hepatitis B increases the risk of cirrhosis in various chronic liver diseases.Aim. Assessment of association between previous hepatitis B and the severity of liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD).Materials and methods. A single-centre cross-sectional trial included 110 HBsAg- and anti-HCV-negative patients with confirmed NAFLD (median (IQR) age 60 (53-66) years). Obesity, type 2 diabetes and dyslipidemia were in 78 (70.9%), 64 (58.2%) and 77 (70%) individuals, respectively. To confirm previous and occult hepatitis B virus (HBV) infection, blood of all participants was examined for anti-HBc (IgG) and HBV DNA. Liver biopsy was performed in 35 patients (31.8%), other patients had transient elastography with steatometry and/or a serum FibroMax™ assay (FibroTest+SteatoTest+NashTest).Results. In 85 patients, liver fibrosis was scored F0-F2 with METAVIR, 25 persons had severe fibrosis (F4 in 23, F3 in 2). Patients with severe fibrosis were significantly older than persons with F0-F2 and had more frequent type 2 diabetes. Anti-HBc was detected in 10 of 25 (40%) patients with F3-F4 and in 7 of 85 (8.2%) persons with F0-F2 (p <0.001). None of anti-HBc-positive individuals had HBV DNA in blood. Presence of anti-HBc was the major factor directly associated with severe liver fibrosis (OR 7.339; 95% CI 2.189-24.604; p = 0.001).Conclusion. Anti-HBc-positive patients with NAFLD have a much higher risk of severe liver fibrosis compared to patients without previous viral hepatitis B.